Multitasking dynamic contrast enhanced magnetic resonance imaging can accurately differentiate chronic pancreatitis from pancreatic ductal adenocarcinoma - Wang, Nan; Gaddam, Srinivas; Xie, Yibin; Christodoulou, Anthony G.; Wu, Chaowei; Ma, Sen; Fan, Zhaoyang; Wang, Lixia; Lo, Simon; Hendifar, Andrew E.; Pandol, Stephen J.; Li, Debiao (Frontiers in Oncology, 2023)
Background and Aims: Accurate differentiation of chronic pancreatitis (CP) and pancreatic ductal adenocarcinoma (PDAC) is an area of unmet clinical need. In this study, a novel Multitasking dynamic contrast enhanced (DCE) magnetic resonance imaging (MRI) technique was used to quantitatively evaluate the microcirculation properties of pancreas in CP and PDAC and differentiate between them. Methods: The Multitasking DCE technique was able to acquire one 3D image per second during the passage of MRI contrast agent, allowing the quantitative estimation of microcirculation properties of tissue, including blood flow Fp, plasma volume fraction vp, transfer constant Ktrans, and extravascular extracellular volume fraction ve. Receiver operating characteristic (ROC) analysis was performed to differentiate the CP pancreas, PDAC pancreas, normal control pancreas, PDAC tumor, PDAC upstream, and PDAC downstream. ROCs from quantitative analysis and conventional analysis were compared. Results: Fourteen PDAC patients, 8 CP patients and 20 healthy subjects were prospectively recruited. The combination of Fp, vp, Ktrans, and ve can differentiate CP versus PDAC pancreas with good AUC (AUC [95% CI] = 0.821 [0.654 – 0.988]), CP versus normal pancreas with excellent AUC (1.000 [1.000 – 1.000]), PDAC pancreas versus normal pancreas with excellent AUC (1.000 [1.000 – 1.000]), CP versus PDAC tumor with excellent AUC (1.000 [1.000 – 1.000]), CP versus PDAC downstream with excellent AUC (0.917 [0.795 – 1.000]), and CP versus PDAC upstream with fair AUC (0.722 [0.465 – 0.980]). This quantitative analysis outperformed conventional analysis in differentiation of each pair. Conclusion: Multitasking DCE MRI is a promising clinical tool that is capable of unbiased quantitative differentiation between CP from PDAC.